Latin America looking for its autonomy: the (im) possibility of concerting between the foreign policies of Brazil and Mexico - Rafael Gustavo Miranda Delgado; Alberto Hoyos Valera (Mural Internacional, 2022)
Latin America as a region, has been losing relevance and agency capacity in the Global Order. Regionalism continues to be a pending task, which is why it is not presented as a unitary actor in the Global Order. Therefore, this research aims to analyse the impact that the divergence of the foreign policies of Brazil and Mexico has had on the search for Latin American autonomy. The hypothesis that guides this research is that the impossibility of concerting the foreign policies of Brazil and Mexico has made it difficult for Latin America to present itself as a unitary regional actor in the Global Order, which prevents its autonomy.